(untitled) (Fiep Bulletin - online, 2014)
This paper presents a proposal that seeks to reinvent the principles of recreation and inclusion in school life . Emerged from the discussions took place in the area of ??knowledge Education for Leisure and Recreation , Graduate Program in Physical Education , Universidade Federal Fluminense in Rio de Janeiro , which resulted in a project known as " Leisure for inclusion : possibilities and emergencies at school " . Used as a guiding point for the design - Leisure education , understanding Leisure as a social event , supported by the cultural , economic and political pillars , without dissociating them in situational analysis , since they are set up between the correlations necessary for understanding the educational process in the school / society in a holistic perspective. Is justified mainly by the need to revisit the pedagogical practices with a view , in fact , the students and the process of knowledge building and training for life , full , plural , critical and emancipatory amplified form , going beyond education for entering the job market. The methodology drew on the qualitative approach , relying on the procedures of educational research as a research participant, participatory planning , dialogical construction with / in the daily , semi -structured questionnaires , interviews oriented individual and / or collective , involving teachers , students and administrators of 5 teaching units of the State of Rio de Janeiro . This article points out the path of Physical Education and Recreation potentiator on the side of the movement and its formative dimensions , and saw the school as a whole , as a mediator of educational processes that will forward to the Leisure critical , democratic and diverse character as demands artistic- aesthetic, physical, motor, cognitive, affective and socio -cultural . The school , in this sense , understand the Leisure as citizens’ rights guaranteed by the constitution , going beyond , revisiting the institutional policies that encourage , their skills and interests .